Penerapan Model Pembelajaran Think Pair Share untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas II SD Negeri 27 Palaluar - Maya Asramaita; Lia Rismawati; Refniwidialistuti (Lembaga Bale Literasi, 2025)
The purpose of this study is to improve the ability of students in grade II of SD Negeri 27 Palaluar in reading comprehension through the application of the Think Pair Share (TPS) learning model. The basis of this study is based on the low achievement of students in learning reading comprehension material, especially in interpreting fable stories. This study applies the Classroom Action Research (CAR) method which is carried out in two stages. The method of collecting information includes observation, documentation, and written tests. The data obtained were analyzed using a qualitative approach to describe the learning process and the approach to assessing the improvement of student learning outcomes. The results of the study showed significant progress in students' reading comprehension skills. In cycle I, the percentage of students who completed learning reached 67% with an average score of 77. After reflecting and improving learning, in cycle II, the percentage of completion increased to 90% with an average score reaching 82. From these results, it can be concluded that the Think Pair Share learning model is effective in improving students' reading comprehension skills actively and cooperatively.